Five Years of Clinical Informatics Board Certification for Physicians in the United States of America - Lehmann, Christoph U.; Gundlapalli, Adi V.; Williamson, Jeffrey J.; Fridsma, Douglas B.; Hersh, William R.; Krousel-Wood, Marie; Ondrula, Christopher J.; Munger, Benson (Yearbook of Medical Informatics, 2018)
Objectives: To review the highlights of the new Clinical Informatics subspecialty including its history, certification requirements, development of and performance on the certification examination in the United States.Methods: We reviewed processes for the development of a subspecialty. Data from board certification examinations were collated and analyzed. We discussed eligibility requirements in the fellowship as well as practice pathways.Results: Lessons learned from the development of the Clinical Informatics subspecialty, opportunities, challenges, and future directions for the field are discussed.Conclusions: There remains a need for fellowship programs and creation and maintenance of a professional home for the subspecialty with the American Medical Informatics Association. Ongoing attention to the currency of the core content is required to maintain an examination designed to test the key concepts within the field of Clinical Informatics.
Keywords: Clinical Informatics; board certification; fellowship training; examination; American Board of Medical Specialties; physicians